Visions of Beauty in the Writings of Dr. Hamida Salih Al-Baldawi: (View and Analysis) - Saeed, Evian Fawzi; Farhan, Jinan Q. (Al-Adab Journal, 2023)
Andalusian poets were able to select aesthetic values from two main sources: nature and man, all of which come through the sensation, harmony and harmony between the poet and the recipient, nature has always influenced the poet through his awareness of its beauty and the extent to which his loving soul is connected to it. The Andalusian poet loved his nature with all its contents, making its moving and static parts aesthetic values of glory and immortality in his poems, until it was known by highlighting all the aesthetic values of nature; and then we found him sharing it with his human feelings in his love and the happiness and misery he feels, making nature with all its molecules his participation in this feeling. Hence our research found paintings that had been written by a creative painter where colors and shadows, provided by the poet with the rhythm and colors of life: calm and noisy, and made it a vibrant heart to live in memories of the past and achieve aesthetic experience in various artistic ways.